1974
DOI: 10.1021/ja00810a042
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric increments of amino acids

Abstract: The dielectric increments for the first ten members of the homologous series of a,w-amino acids, together with those for a number of rigid or "pseudorigid" molecules, have been calculated from dielectric constants in aqueous solution. The results suggest that the flexible molecules exist in their most extended conformations and that solvent effects contribute significantly to the observed dielectric increments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…A number of authors have reported temperature-dependent values of the dipole moment µ for R-alanine, [54][55][56][57][58] β-alanine, 54,55,57,59,60 and proline. 61,62 Most of these are estimates of the effective dipole moment in dilute solutions from molar dielectric increments δ, as defined by the Kirkwood equation: 63,64 where µ is expressed in Debye and δ is expressed in m 3 ‚mol -1 .…”
Section: Contributions To V°mentioning
confidence: 99%
“…A number of authors have reported temperature-dependent values of the dipole moment µ for R-alanine, [54][55][56][57][58] β-alanine, 54,55,57,59,60 and proline. 61,62 Most of these are estimates of the effective dipole moment in dilute solutions from molar dielectric increments δ, as defined by the Kirkwood equation: 63,64 where µ is expressed in Debye and δ is expressed in m 3 ‚mol -1 .…”
Section: Contributions To V°mentioning
confidence: 99%
“…In the previous paper of this series we examined the influence of the charges upon the partial molar volumes, hydrophobic hydration, and orientation of the solvent molecules around the hydrocarbon portion of a variety of aminoacids in water. Individual electrostrictive volumes of the solvent, caused by the presence of the charged groups, were evaluated from their partial molar volumes by comparison with the corresponding alkylammonium salts and sodium alkylcarboxylates, using the approaches summarized by eqn (1) and ( 2 V" = aVw+b (2) where the parameters have their previously assigned meaning^.^ It was confirmed that the major effect on electrostrictive volume, E, of the solvent molecules by aminoacids comes from the positively charged amino group, and that E could be expressed as the sum of electrostriction and hydrophobic hydration effects [eqn (3)] E = V"+VH.…”
mentioning
confidence: 99%
“…A number of studies [34,45,46] have shown that intramolecular pairing does not occur with zwitterionic additives. In other words, the two charged end groups do not wrap around to form an ion pair with themselves.…”
Section: Dielectric Constantmentioning
confidence: 99%